Effectiveness of Cau Raja (Green Grass Jelly with Red Ginger Flavor) on Blood Pressure in Pregnant Women with Hypertension - Susanti Susanti; Mardiyono Mardiyono; Dina Indrati Dyah Sulistyowati (Journal of Maternal and Child Health, 2026)
Background: Hypertension in pregnancy is a global health problem that can increase the risk of complications for the mother and fetus. Cau Raja is a combination of 100 grams of Green Grass Jelly (Cyclea barbata Miers) and 25 mg of dried Red Ginger (Zingiber officinale var. Rubrum), containing 24 mg of flavonoids and 107 mg of potassium. These compounds can lower blood pressure in pregnant women with mild hypertension. The purpose of this study was to prove the effectiveness of Cau Raja in reducing blood pressure in pregnant women with mild hypertension. Subjects and Methods: This study used a True Experimental and Pretest-Posttest with Control Group Design. The study location was Purwokerto Timur I Community Health Center. Data collection was conducted in November 2025. The intervention group consisted of 250 ml of Cau Raja (green grass jelly with red ginger flavor) for 14 days and a control group given therapy according to SOP. The dependent variable studied was blood pressure, and the independent variables were Cau Raja (green grass jelly with red ginger flavor) and therapy according to SOP. The analysis technique used a Paired Sample T-Test. Results: The average systolic blood pressure in the intervention group after being given Cau Raja (green grass jelly with red ginger flavor) was lower (Mean = 118.88; SD = 7.16) compared to before the intervention (Mean = 129.81; SD = 4.96) and was statistically significant (p <0.001). The average diastolic blood pressure in the intervention group after being given Cau Raja (green grass jelly with red ginger flavor) was lower (Mean = 76.50; SD = 5.36) compared to before the intervention (Mean = 83.94; SD = 4.37) and was statistically significant (p <0.001). Conclusion: Giving Cau Raja (green grass jelly with red ginger flavor) has been proven to be effective in lowering blood pressure in pregnant women with mild hypertension, so it can be used as a safe and practical non-pharmacological therapy alternative.